How Mycobacterium tuberculosis drug resistance has shaped anti-tubercular drug discovery - Bhagwat, Amala; Deshpande, Aditi; Parish, Tanya (Frontiers in Cellular and Infection Microbiology, 2022)
Drug resistance is an increasing problem for the treatment of tuberculosis. The prevalence of clinical isolates with pre-existing resistance needs to be considered in any drug discovery program. Non-specific mechanisms of resistance such as increased efflux or decreased permeability need to be considered both in developing individual drug candidates and when designing novel regimens. We review a number of different approaches to develop new analogs and drug combinations or improve efficacy of existing drugs that may overcome or delay the appearance of clinical resistance. We also discuss the need to fully characterize mechanisms of resistance and cross- resistance to existing drugs to ensure that novel drugs will be clinically effective.